2021
DOI: 10.3390/microorganisms9030647
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Gut Microbiota Recovery after Antibiotic Exposure in Young and Old Mice (A Pilot Study)

Abstract: Antibiotics have improved survival from previously deadly infectious diseases. Antibiotics alter the microbial composition of the gut microbiota, and these changes are associated with diminished innate immunity and decline in cognitive function in older adults. The composition of the human microbiota changes with age over the human lifespan. In this pilot study, we sought to identify if age is associated with differential recovery of the microbiota after antibiotic exposure. Using 16S rRNA gene sequencing, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…In the elderly, antibiotic exposure was linked to microbiota diversity loss ( Ng et al, 2019 ; Ramirez et al, 2020 ). Recently, the age factor was further demonstrated in a mouse model, where older mice with 10 days of antibiotics could not achieve gut bacteria recovery after 6 months and even at the end of the study ( Laubitz et al, 2021 ). These results revealed that age is a critical factor associated with gut microbiome recovery after antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the elderly, antibiotic exposure was linked to microbiota diversity loss ( Ng et al, 2019 ; Ramirez et al, 2020 ). Recently, the age factor was further demonstrated in a mouse model, where older mice with 10 days of antibiotics could not achieve gut bacteria recovery after 6 months and even at the end of the study ( Laubitz et al, 2021 ). These results revealed that age is a critical factor associated with gut microbiome recovery after antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The reads were processed, and data analyzed as we described previously. 32 , 33 Briefly, de-multiplexing was performed using idemp script ( https://github.com/yhwu/idemp ). Filtering, dereplication, sample inference, chimera identification, and merging of paired-end reads was done with a reference-free Divisive Amplicon Denoising Algorithm 2 (Dada2, version 1.18.0) 34 package in RStudio (version 1.3.1093 with R version 4.0.3).…”
Section: Methodsmentioning
confidence: 99%
“…The reads were processed, and data analyzed as we described previously. 32,33 Briefly, de-multiplexing was performed using idemp script (https://github.com/yhwu/idemp). Filtering, dereplication, sample inference, chimera identification, and merging of paired-end reads was done with 3).…”
Section: Microbiome Analysismentioning
confidence: 99%
“…The data were analyzed as described previously 57 . Briefly, the fastq files were demultiplexed with the idemp script ( https://github.com/yhwu/idemp ), filtering, dereplication, chimera identification, and merging of paired-end reads were performed with dada2 R package 58 .…”
Section: Methodsmentioning
confidence: 99%